Impaired path integration in mice with disrupted grid cell firing - Gil, Mariana; Ancău, Mihai; Schlesiger, Magdalene; Neitz, Angela; Allen, Kevin; Monyer, Hannah (Nature neuroscience, 2018)
Path integration (PI) is a highly conserved, self-motion-based navigation strategy. Since the discovery of grid cells in the medial entorhinal cortex, neurophysiological data and computational models have suggested that these neurons serve PI. However, more direct empirical evidence supporting this hypothesis has been missing due to a lack of selective manipulations of grid cell activity and suitable behavioral assessments. Here we report that selective disruption of grid cell activity in mice can be achieved by removing NMDA glutamate receptors from the retro-hippocampal region and that disrupted grid cell firing accounts for impaired PI performance. Notably, the genetic manipulation did not affect the activity of other spatially selective cells in the medial entorhinal cortex and the hippocampus. By directly linking grid cell activity to PI, these results contribute to a better understanding of how grid cells support navigation and spatial memory.